Pulmonary Interstitial Glycogenosis: A Reversible Underlying Condition Associated With D-Transposition of the Great Arteries and Severe Persistent Pulmonary Hypertension. (July 2015) - Sanchez-de-Toledo, Joan; González-Peris, Sebastià; Gran, Ferran; Gregoraci, Angela; Ferreres, Joan Carles; Ruiz, Cèsar W.; Balcells, Joan; Abella, Raul F.
Transposition of the great arteries with intact ventricular septum and persistent pulmonary hypertension (TGA-IVS PPHN) is a rare association with a poor prognosis. We report the case of a term newborn with TGA-IVS PPHN successfully managed with perioperative extracorporeal membrane oxygenation (ECMO) and aggressive pulmonary vasodilation therapy that underwent successful arterial switch procedure. A lung biopsy obtained during the surgical procedure showed pulmonary interstitial glycogenosis, a reversible condition. Concerns over left ventricle deconditioning after ECMO could be minimized with appropriate management and monitoring of the ductus arteriosus and appropriate timing of surgery.